Extending delone and mclean success model with diffusion of innovation theory factors for flood early warning and response system success model : a case study at pahang civil defence department - Waleed Abdulmaged, Hammood (2021)
In terms of population affected, the region involved, frequency, social-economic damage, and flood period, floods are a major natural disaster in Malaysia. That emphasizes the value of systematic and effective flood control, which necessitates government agencies improving their efficiency through technical advancement. The Flood Early Warning and Response System (FEWRS) success model is critical to prevent loss of life and property. It ensures that all stakeholders have the correct information and have the appropriate actions and response information. It should have some successful accessibility functionality and success elements of its strategic knowledge access and show, but current FEWRS success model lacks and often do not adequately have information on flood hazards to minimize their effects at a local level and save the lives of the people. For researchers, practitioners, and managers, determining the success of an Information System (IS) remains a significant concern. Therefore, the research objective of this study is to identify the success factors that affect the implementation of enhance FEWRS success model, to deploy the enhanced FEWRS success model. Moreover, to validate the enhanced FEWRS success model using the statistical analysis methods. This research focuses on two theoretical frameworks: DeLone and McLean (DLML) IS success model and Diffusion of Innovation Theory (DOI). These two theories have been found the most appropriate to be adopted for the FEWRS success model. They are merged to understand and explore the successful contingent related to IS implementation. DLML and DOI are among the most utilized theories applied in research relating to systems, technology, and information use. DOI theory states that the organization’s innovation and organizational characteristics and the environment in which it operates can influence the diffusion and success of Information Technology (IT) initiatives. The enhanced FEWRS success model was validated through the development of the enhanced FEWRS model and the use of statistical analysis methods. To validate the FEWRS success model, this study employs the Partial Least Squares-Structural Equation Modelling (PLS-SEM). Data were collected through a questionnaire survey administered to 141 employees from Kuantan Civil Defence Department (CDD) in Pahang state, Malaysia. Preliminary survey had been done before going further into the study to show the importance of the research. The results suggest that information quality, system quality, service quality, and compatibility have a positive effect on user satisfaction of the enhanced FEWRS success model with (P-value = 2.359, 0.204, 0218, 0.445, and 0354. These factors have a strong significant relationship with the user’s satisfaction. However, the relative advantage has a positive effect on user satisfaction but was not supported with (P-value = 0.015). On the other hand, complexity has a negative effect on user satisfaction of the FEWRS with (P-value = - 0.114). Therefore, complexity was found to have a significant relationship with user satisfaction. Furthermore, user satisfaction has positively affected the success of the FEWRS. In the light of the FEWRS success model presence in the flood disaster and other natural disasters, the study findings will act as a guide for strengthening government policy and the public sector. Moreover, the results have a significant contribution by validating and extending the DLML with DOI factors and providing various implications to the research, theory, and practice.